HYPODYNAMY AS ONE OF THE CURRENT CAUSES OF THE DEVELOPMENT OF CERVICAL OSTEOCHONDROSIS - Zarichniuk, I. R.; Zhyhulova, E. O.; Zaikin, A. V. (Rehabilitation and Recreation, 2022)
The article provides a theoretical overview of modern views on the role of hypodynamia in the development of cervical osteochondrosis. Currently, low physical activity contributes to the development of osteochondrosis, especially affecting people of working age. The purpose of this work was to conduct an analysis of data from the scientific and methodological literature on the relevance of the impact of hypodynamia on the development of cervical osteochondrosis. The main signs of hypodynamia in cervical osteochondrosis are considered. Social and psychological reasons for the development of hypodynamia, possible diseases arising as a result of its appearance are analyzed. Current means of prevention and prevention of hypodynamia, with subsequent development of cervical osteochondrosis, are proposed. To achieve the research objectives, we used the following research methods: theoretical: analysis of literary sources related to the researched problem, systematization of data on research issues, obtained in the process of processing scientific articles, textbooks, manuals, dissertation studies; pedagogical: setting goals and objectives, determining the purpose of the study, presenting the results of the study in relation to the subject. The disease of cervical osteochondrosis of the spine is gaining more and more social significance due to the constant growth of the number of patients. It occupies one of the first places in the structure of diseases with temporary loss of working capacity and disability of the population of Ukraine. This disease is becoming more and more relevant due to the constant increase in the number of patients. Hypodynamia associated with work activities increases the morpho-functional deviations of the spine that are present in a significant number of the population, which progress over the years. Long-term restriction of movement mode by a person, due to the specificity of many modern professions, is one of the main causes of cervical osteochondrosis. This leads to chronic overstrain, fatigue and weakening of the muscles, changes in the value of cervical lordosis. The main indicators of hypodynamia are limitation of the motor activity of the body, insufficiency of movements. Movement is what the body needs for stable work, and it is precisely this that is the key to high performance, good health and good health. The use of the proposed means of prevention and prevention of the occurrence of hypodynamia, with the subsequent development of cervical osteochondrosis, allows you to effectively influence a person’s working capacity, his health and well-being.